Evaluation of the behavior of two artificial marshes installed in series with Phragmites australis for the treatment of domestic wastewater - Quipuzco Ushñahua, Lawrence Enrique (2002)
The present investigation was to evaluate the behavior of two constructed wetlands in series with Phragmites australis for the treatment of domestic sewage. The wastewater source was captured drainage network of the Universidad Nacional Agraria La Molina. The wastewater was conducted by pipes to a sedimentation tank and cylinders and subsequently distributed to two reservoirs installed in series planted with Phragmites australis : A Horizontal followed a vertical marsh swamp. The porous medium marsh consisted of gravel and sand substrates . The marshes were operating with subsurface flow under conditions of continuous power . Performance monitoring of the treatment system was conducted during the months of November 2000 and January 2001, with weekly sampling . In analyzing the behavior of TSS and BOD5 in the horizontal marsh A removal of 97.2 % and 79.6 % were obtained. The horizontal swamp the greater removal of organic matter due to the effective mineralization was performed. In contrast , poor performance was observed in the vertical marsh. COD is largely eliminated in the horizontal marsh (84.3%) . At this stage the sand filter was responsible for most COD removal . The sulfate removal level stages in the processing system was significant for both reservoirs with 71.2% for the horizontal and 52.85 % swamp for vertical swamp . The level of efficiency in the removal of fecal coliforms and intestinal parasites in the treatment system was significant percentages reaching 98 and 62 % respectively.